Impact of Microphytobenthos Photosynthesis on the Characteristics of the Echo Signal from Baltic Sandy Sediments - GORSKA, Natalia; KOWALSKA-DUDA, Ewa; MARSZAL, Jacek; SCHMIDT, Jan Henryk; KLUSEK, Zygmunt (Archives of Acoustics, 2015)
The understanding the influence of biological processes on the characteristics of the signals backscattered by the sea floor is crucial in the development of the hydroacoustical benthic habitat classification techniques. The impact of the microphytobenthos photosynthesis on the acoustical backscattering properties of the Atlantic sandy sediments was previously demonstrated by Holliday et al. (2004) and Wildman and Huettel (2012).To account for the sensitivity of the hydroacoustical classification techniques to the backscattering properties of local marine sediments, it is important to understand the microphytobenthos photosynthesis impact for the Baltic Sea where the techniques are being actively developed now. This is the main motivation of the paper.In the paper the influence of the microphytobenthos photosynthesis on the characteristics of the echo signals reflected by sandy sediments in the typical Baltic temperature and the salinity conditions is discussed. The interdisciplinary multiday laboratory experiment was conducted to study the impact of benthic microalgal photosynthesis on the characteristics of the echo signal reflected by sandy sediments. Hydroacoustical data were collected under controlled constant light, temperature and salinity conditions. The oxygen content at different levels of the water column was simultaneously monitored.